Exome sequencing implicates genetic disruption of prenatal neuro-gliogenesis in sporadic congenital hydrocephalus. - Jin, Sheng Chih; Dong, Weilai; Kundishora, Adam J; Panchagnula, Shreyas; Moreno-De-Luca, Andres; Furey, Charuta G; Allocco, August A; Walker, Rebecca L; Nelson-Williams, Carol; Smith, Hannah; Dunbar, Ashley; Conine, Sierra; et al. (Nat Med, 2020)
Congenital hydrocephalus (CH), characterized by enlarged brain ventricles, is considered a disease of excessive cerebrospinal fluid (CSF) accumulation and thereby treated with neurosurgical CSF diversion with high morbidity and failure rates. The poor neurodevelopmental outcomes and persistence of ventriculomegaly in some post-surgical patients highlight our limited knowledge of disease mechanisms. Through whole-exome sequencing of 381 patients (232 trios) with sporadic, neurosurgically treated CH, we found that damaging de novo mutations account for >17% of cases, with five different genes exhibiting a significant de novo mutation burden. In all, rare, damaging mutations with large effect contributed to ~22% of sporadic CH cases. Multiple CH genes are key regulators of neural stem cell biology and converge in human transcriptional networks and cell types pertinent for fetal neuro-gliogenesis. These data implicate genetic disruption of early brain development, not impaired CSF dynamics, as the primary pathomechanism of a significant number of patients with sporadic CH.
Keywords: Brain; Cerebral Ventricles; Exome; Female; Genetic Predisposition to Disease; Humans; Hydrocephalus; Male; Mutation; Neural Stem Cells; Neurogenesis; Neuroglia; Transcription Factors; Tripartite Motif Proteins; Ubiquitin-Protein Ligases; Whole Exome Sequencing

A genome-wide case-only test for the detection of digenic inheritance in human exomes. - Kerner, Gaspard; Bouaziz, Matthieu; Cobat, Aurelie; Bigio, Benedetta; Timberlake, Andrew T; Bustamante, Jacinta; Lifton, Richard P; Casanova, Jean-Laurent; Abel, Laurent (Proc Natl Acad Sci U S A, 2020)
Whole-exome sequencing (WES) has facilitated the discovery of genetic lesions underlying monogenic disorders. Incomplete penetrance and variable expressivity suggest a contribution of additional genetic lesions to clinical manifestations and outcome. Some monogenic disorders may therefore actually be digenic. However, only a few digenic disorders have been reported, all discovered by candidate gene approaches applied to at least one locus. We propose here a two-locus genome-wide test for detecting digenic inheritance in WES data. This approach uses the gene as the unit of analysis and tests all pairs of genes to detect pairwise gene × gene interactions underlying disease. It is a case-only method, which has several advantages over classic case-control tests, in particular by avoiding recruitment of controls. Our simulation studies based on real WES data identified two major sources of type I error inflation in this case-only test: linkage disequilibrium and population stratification. Both were corrected by specific procedures. Moreover, our case-only approach is more powerful than the corresponding case-control test for detecting digenic interactions in various population stratification scenarios. Finally, we confirmed the potential of our unbiased, genome-wide approach by successfully identifying a previously reported digenic lesion in patients with craniosynostosis. Our case-only test is a powerful and timely tool for detecting digenic inheritance in WES data from patients.
Keywords: Craniosynostoses; Epistasis, Genetic; Exome; Genetic Linkage; Genetic Variation; Genome-Wide Association Study; High-Throughput Nucleotide Sequencing; Humans; Models, Genetic; Multifactorial Inheritance; Whole Exome Sequencing

De novo mutations in inhibitors of Wnt, BMP, and Ras/ERK signaling pathways in non-syndromic midline craniosynostosis. - Timberlake, Andrew T; Furey, Charuta G; Choi, Jungmin; Nelson-Williams, Carol; Loring, Erin; Galm, Amy; Kahle, Kristopher T; Steinbacher, Derek M; Larysz, Dawid; Persing, John A; Lifton, Richard P (Proc Natl Acad Sci U S A, 2017)
Non-syndromic craniosynostosis (NSC) is a frequent congenital malformation in which one or more cranial sutures fuse prematurely. Mutations causing rare syndromic craniosynostoses in humans and engineered mouse models commonly increase signaling of the Wnt, bone morphogenetic protein (BMP), or Ras/ERK pathways, converging on shared nuclear targets that promote bone formation. In contrast, the genetics of NSC is largely unexplored. More than 95% of NSC is sporadic, suggesting a role for de novo mutations. Exome sequencing of 291 parent-offspring trios with midline NSC revealed 15 probands with heterozygous damaging de novo mutations in 12 negative regulators of Wnt, BMP, and Ras/ERK signaling (10.9-fold enrichment, = 2.4 × 10). had 4 de novo and 14 transmitted mutations; no other gene had more than 1. Four familial NSC kindreds had mutations in genes previously implicated in syndromic disease. Collectively, these mutations contribute to 10% of probands. Mutations are predominantly loss-of-function, implicating haploinsufficiency as a frequent mechanism. A common risk variant near increased the penetrance of mutations and was overtransmitted to patients with de novo mutations in other genes in these pathways, supporting a frequent two-locus pathogenesis. These findings implicate new genes in NSC and demonstrate related pathophysiology of common non-syndromic and rare syndromic craniosynostoses. These findings have implications for diagnosis, risk of recurrence, and risk of adverse neurodevelopmental outcomes. Finally, the use of pathways identified in rare syndromic disease to find genes accounting for non-syndromic cases may prove broadly relevant to understanding other congenital disorders featuring high locus heterogeneity.
Keywords: Adult; Animals; Bone Morphogenetic Proteins; Child; Child, Preschool; Cranial Sutures; Craniosynostoses; Exome; Female; Humans; Male; MAP Kinase Signaling System; Mutation; Osteogenesis; Penetrance; Phenotype; ras Proteins; Sequence Analysis, DNA; Signal Transduction; Smad6 Protein; Whole Exome Sequencing

Two locus inheritance of non-syndromic midline craniosynostosis via rare and common alleles. - Timberlake, Andrew T; Choi, Jungmin; Zaidi, Samir; Lu, Qiongshi; Nelson-Williams, Carol; Brooks, Eric D; Bilguvar, Kaya; Tikhonova, Irina; Mane, Shrikant; Yang, Jenny F; Sawh-Martinez, Rajendra; Persing, Sarah; et al. (Elife, 2016)
Premature fusion of the cranial sutures (craniosynostosis), affecting 1 in 2000 newborns, is treated surgically in infancy to prevent adverse neurologic outcomes. To identify mutations contributing to common non-syndromic midline (sagittal and metopic) craniosynostosis, we performed exome sequencing of 132 parent-offspring trios and 59 additional probands. Thirteen probands (7%) had damaging de novo or rare transmitted mutations in , an inhibitor of BMP - induced osteoblast differentiation (p<10). mutations nonetheless showed striking incomplete penetrance (<60%). Genotypes of a common variant near that is strongly associated with midline craniosynostosis explained nearly all the phenotypic variation in these kindreds, with highly significant evidence of genetic interaction between these loci via both association and analysis of linkage. This epistatic interaction of rare and common variants defines the most frequent cause of midline craniosynostosis and has implications for the genetic basis of other diseases.
Keywords: Alleles; Bone Morphogenetic Protein 2; Craniosynostoses; Exome; Genetic Association Studies; Humans; Infant; Mutation; Penetrance; Sequence Analysis, DNA; Smad6 Protein